EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PESERTA DIDIK SEKOLAH DASAR - Mutakarikah; Encep Andriana; Siti Rokmanah (STKIP Subang, 2023)
This research was motivated by the lack of students' ability to think critically, where this research was aimed at finding out how effective elementary school students' thinking was with the application of the problem-based learning model. This research uses qualitative research using a description methodology that uses words in its description. The data collection technique used was through interviews and observations where the subjects in this research were grade V elementary school students at SDN Cipocok Jaya 2. The results obtained in this study showed that there was an improvement before and after the implementation of the problem-based learning model in classroom learning. With the application of this problem-based learning model, most students' thinking becomes more critical than before the application of the problem-based learning model.